VARIASI KONSENTRASI PEREKAT TAPIOKA DAN ARANGCANGKANG BIJI BUAH PICUNG (Pangium edule Reinw.) TERHADAP KUALITAS BRIKET ARANG - Amalan Subekti; Hanum Hamzah; Akhyar Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The shell of picungfruit seedscontainsa quite high amount ofactivated carbonwhich isnot yet been optimally utilized. This research aims to utilized theshell of picung fruit seeds asmain ingredientinthe making of charcoal briquettes and to get the best concentration of tapioca adhesive.The method of this research used Completely Random Design (CRD) whichconsist of5treatment and eachtreatment was repeated 3 times.The treatmentofP1 was 97%: 3%, P295%: 5%, P393%: 7%, P491%: 9%,P589%: 11%. continued with Duncan New Multiple Range Test (DNMRT) at 5% level. Result of the analysis showed that the variation range of tapiocaadhesive of charcoal briquettes was significantly effected on moisture, ash, combustion rate level, and the level of the substance evaporation, and the heat value. Based on this research, the best treatment was ratio of charcoal and tapioca adhesives, wich were P1 (97% : 3%), average content of moisture 2.92%, ash 3.52%, combustion rate 43×10-3, substance evaporation 15.32%, and heat value 6.554 cal/g. Keywords: Briquettes, tapioca starch, seedsshellpicung fruit